(untitled) (Research, Society and Development, 2022)
This study aimed to describe the participation of the elderly population of the city of Pelotas/RS, in the 2020 elections. A descriptive, retrospective study, with data obtained regarding the 2020 election, from the Information Panel on the elderly, organized by the Associação Brasileira de apoio à Maturidade Solidária (ABAMS). Of the elderly population in 2020, in the city studied, 32,363 are required to vote, these data correspond to people between 60 and 69 years of age, a number that expresses 61.7% of the total elderly population. This population corresponds to 15.3% of the voting population of this municipality and of these 57% are female. As a thought, this study focuses on the appreciation of the elderly population in relation to their participation in political choices, since people over 60 years of age are an expressive group, which may have made a difference in this evaluated election and could increasingly being responsible for future choices, also thinking about the perspective of future aging.